Kualitas Pembelajaran Aparatur Dalam Penyelenggaraan Pemerintahan Desa di Kabupaten Bogor - Sitti Aminah (Jurnal Kebijakan Pembangunan, 2018)
The ability of human resources of the village government apparatus is considered inadequate to carry out the authority stipulated in Law Number 6 of 2014 concerning Villages. The study aims to analyze the accuracy of the learning process in increasing capacity of village government apparatus program or PKAD. Data were collected in August and September 2016 in Bogor regency and analyzed using descriptive statistics. The results of the study show that the accuracy of the learning process of PKAD training is an adequate category. The study recommends improving the learning facilities, adjustment of the learning method by increasing practices, especially for village financial management materials, adding time of training and improving intensity both dialogue and sharing knowledge among participants and facilitators also improving the quality of facilitators. abstrak Kemampuan sumberdaya manusia aparat peme rintah desa dinilai kurang memadai untuk melaksanakan kewenangan yang diatur dalam UU Nomor 6 Tahun 2014 tentang Desa. Tujuan kajian adalah menganalisis ketepatan proses pembelajaran dalam program peningkatan kapasitas aparatur pemeritah desa atau PKAD. Data dikumpulkan pada bulan Agustus dan September 2016 di Kabupaten Bogor dan dianalisis menggunakan statistik deskriptif. Hasil studi menunjukan bahwa ketepatan proses pembelajaran diklat PKAD tergolong cukup memadai. Rekomendas i kajian adalah melakukan perbaikan program diklat PKAD melalui peningkatan sarana dan fasilias belajar, penyesuaian metode belajar dengan memperbanyak praktek terutama untuk materi pengelolaan keuangan desa, menambah lamanya waktu belajar dan meningkatkan dialog dan berbagi pengetahuan diantara peserta dan fasilitator serta meningkatkan kualitas fasilitator.